2010
DOI: 10.1590/s1808-86942010000500015
|View full text |Cite
|
Sign up to set email alerts
|

Resultados do Balance Rehabilitation Unit na Vertigem Posicional Paroxística Benigna

Abstract: Post urography is a useful new tool to study the influence of vestibular diseases on balance.Aim: to compare the results from the Balance Rehabilitation Unit (BRU) static posturography in elderly patients with Benign Paroxysmal Positional Vertigo (BPPV), before and after Epley's maneuver.Materials and Methods: a prospective study of 20 elderly patients with a diagnosis of BPPV. The patients underwent static posturography and the limit of stability (LE) and ellipse area were measured. We also applied the Dizzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Vascular stress of the anterior vestibular artery may reduce blood flow to the labyrinth and hence cause serious damage to the macula and otoconia detachment (24). Ballester reported that vertigo in BPPV patients with Ménière's disease required longer time to recover (25). This phenomenon may also be influenced by the balance disorder between endolymphatic absorption and utricle (26).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular stress of the anterior vestibular artery may reduce blood flow to the labyrinth and hence cause serious damage to the macula and otoconia detachment (24). Ballester reported that vertigo in BPPV patients with Ménière's disease required longer time to recover (25). This phenomenon may also be influenced by the balance disorder between endolymphatic absorption and utricle (26).…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao equilíbrio semiestático, observou-se aumento significante da área do limite de estabilidade (LE) em idosos com VPPB, com redução da área do centro depressão (COP) e da velocidade de oscilação corporal (VOC) em todas as condições analisadas por meio de plataforma de força estática e sistema de realidade virtual (Balance Rehabilitation Unit -BRU TM ), após manobra de Epley [17][18][19] . Esses dados sugerem que o tratamento possibilitou maior controle postural e menor dependência das pistas visuais para a manutenção do equilíbrio postural na postura vertical semiestática.…”
Section: Avaliação Clínico-funcionalunclassified
“…A posturografia do Balance Rehabilitation Unit (BRU TM ) revelou-se um método laboratorial que permite identificar alterações do equilíbrio postural em pessoas com VPPB por meio de perturbação dos sistemas sensoriais. Santana e Kasse et al 17,18 observaram aumento significante da área do LE e redução nos valores da área do COP e da VOC após manobra de Epley em idosos, em diferentes condições de estímulos sensoriais. Os resultados obtidos referem que o tratamento possibilitou maior controle postural e menor dependência de pistas visuais para a manutenção do equilíbrio postural na postura vertical semiestática, concordando com Monteiro et al 19 , os quais afirmaram que alterações dos valores da VOC e da área de elipse podem ser considerados de grande utilidade na bateria de testes que compõe a avaliação otoneurológica.…”
Section: Recomendações Pós-tratamentounclassified
“…These consequences appear mainly during the acute moments of vertigo; however, they may have some implications between crises with functional and emotional consequences. Thus, the knowledge of the characteristics of global balance in elderly patients with BPPV must be enhanced and variables that may be associated with balance loss and postural control must be identified to implement targeted prevention and rehabilitation strategies 1,16,17 . Currently, limited literature analyses the functional aspects and quality of life of the elderly population after BPPV treatment, specifically focusing on their postural control.…”
Section: Introductionmentioning
confidence: 99%